Reflection article on the covid 19 post-pandemic digital consumer profile study (2024)
This article is part of the research project: "Profile of the digital consumer post Covid-19 pandemic in the gastronomic sector of the department of Córdoba. Segment: fast food fast food emerging local brands" with this is intended to make a reflection on the impact of the Covid-19 pandemic in various variables of economic and social type globally; through a detailed search of original documents related to our project, mainly in the SCOPUS database. Among some of the results found in a partial sample is that the pandemic has influenced many variables among which we can highlight the changes in purchasing habits; in addition, the pandemic has forced companies to change many processes, among which stands out their sales and payment methods. In conclusion, the effects of the pandemic have caused major changes in the performance of all organizations, many of these effects are uncertain and unpredictable, which forces companies to be prepared with strategies to address the problem during and after the crisis in order to mitigate the potential economic impacts in the long term.